MODEL APLIKASI E-MARKET SEBAGAI SARANA PROMOSI DAN TUKAR MENUKAR INFORMASI ANTARA PENJUAL DAN PEMBELI - Frans Richard Kodong; Wilis Kaswidjanti; Arif Setiyawan (Jurusan Teknik Informatika, 2012)
With the Internet can facilitate human life in all areas, not least in the field of buying and selling and promotion, where the internet buying and selling process can be done more easily, for those sellers can easily Promote goods that are sold to consumers that they can easily find items needs, but to create a website selling a store still require substantial funds, and therefore required a new method in the business world, the market because the process is done electronically using electronic media and the internet is a method of electronic stores. The methode is to collect various types of shops into a website. In this application there is a facility newsletter that can be commented on by the other accountowners. In this way the expected communication between sellers and buyers and store owners to one another more closely, so that in terms of social aspects and the business is very profitable because it can add to relationships and friendships. This application will be made using the language of the web-based pemorgraman JSP and servlets, jquery andajax as a transport request to the MySQL database as the media supported penyimpanadata. The method used in making this application is GRAPLLE. E-market applications asa container or a place and means of promotion and inforamasi exchange between sellerand buyer, in line with advances in technology to achieve their social and economic needs of human beings, so that economic growth particularly medium rise, because the e-marketthrough the application of this variation and reach a wider market, this is due to the use ofinternet technology that knows no time and space.